-6n-5=1

Simple and best practice solution for -6n-5=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6n-5=1 equation:


Simplifying
-6n + -5 = 1

Reorder the terms:
-5 + -6n = 1

Solving
-5 + -6n = 1

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + -6n = 1 + 5

Combine like terms: -5 + 5 = 0
0 + -6n = 1 + 5
-6n = 1 + 5

Combine like terms: 1 + 5 = 6
-6n = 6

Divide each side by '-6'.
n = -1

Simplifying
n = -1

See similar equations:

| 3n/4-3=60 | | 66=-66+12x | | 2x*x-2x-1=0 | | P^2-2p-35= | | n/6+3=10 | | 55=-55+10x | | 18-2x-2x-2=56 | | n/4-7=9 | | 3x^2-(2x-4)=3+3x^2 | | 6x-52=44 | | 0.7(8x+16)=1.8-(x-2) | | n/4+2=11 | | 142=5x+57 | | 3x+y=-29 | | 3x^2-(2x-4)=3+3x | | 59=-84+11x | | 1=10-c | | 7x+x+2=29 | | 5x+15+30+35= | | 10x+32=152 | | 29=-43+4x | | 4k-9=-33 | | 179=6x+77 | | 0.128-0.035v=-0.072v+0.235 | | 6(x-7)=-20-5x | | 81=-55+8x | | 3n+4=2n | | 32x=278 | | 50=7x-13 | | 40=(2x)(x-1)(x-4) | | 23x=82.7 | | 7x+5.50(x+100)=3825 |

Equations solver categories